Design Tool Analysis of Prenatal Care Management for Midwife in Rural Area - Ulfah, Ulfah; Supriyanto, Eko; Fitri, Fitri (JURNAL IBU DAN ANAK, 2018)
Purpose of this research is to design a tool analysis in prenatal care management for midwife in rural area. The case study will conduct at Kampar Regency, Riau Province, Indonesia. Data collection methods divided into three aspects: policy, legal and financial. Finding of this paper are points in questionnaire and clustering analysis on midwife based on background, knowledge, and working experience. This paper will become a tool to measure service level of prenatal care management in rural area. Further research will measure prenatal care management through spread of questionnaires on midwife